2017
DOI: 10.1108/lodj-10-2015-0229
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level study of servant leadership on creativity

Abstract: Purpose The purpose of this paper is to explore the influencing mechanism of servant leadership on employee and team creativity based on efficacy theory. Specifically, the study intends to develop a model of efficacy beliefs that mediates the relationships between servant leadership, employee creativity, and team creativity at different levels. The study also aims to investigate the moderating effects of team power distance on the relationships between servant leadership, creative self-efficacy, and team effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
172
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(192 citation statements)
references
References 59 publications
(155 reference statements)
18
172
1
1
Order By: Relevance
“…Of these predictors, leadership/supervisory behavior has been the most acknowledged predictor of IWB, due to leaders'/supervisors' role modeling and reward-punishment capacity (Bos-Nehles et al, 2017;Javed et al, 2018;Tu et al, 2018). While extant research has identified positive leadership/supervisory behaviors (i.e., ethical, servant, and inclusive leadership behaviors) (Javed et al, 2018;Yang et al, 2017;Yidong and Xinxin, 2013) as positive predictors of IWB, relatively little is known about the impact of negative leadership/supervisor behaviors as negative predictors of IWB, with the exception of abusive supervision (Dong et al, 2012;Lee et al, 2018;Rousseau and Aubé, 2018). Thus, to extend the literature on the relationship between negative supervisory behavior and IWB, we investigate the effect of SKHS on supervisee IWB.…”
Section: Innovative Work Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Of these predictors, leadership/supervisory behavior has been the most acknowledged predictor of IWB, due to leaders'/supervisors' role modeling and reward-punishment capacity (Bos-Nehles et al, 2017;Javed et al, 2018;Tu et al, 2018). While extant research has identified positive leadership/supervisory behaviors (i.e., ethical, servant, and inclusive leadership behaviors) (Javed et al, 2018;Yang et al, 2017;Yidong and Xinxin, 2013) as positive predictors of IWB, relatively little is known about the impact of negative leadership/supervisor behaviors as negative predictors of IWB, with the exception of abusive supervision (Dong et al, 2012;Lee et al, 2018;Rousseau and Aubé, 2018). Thus, to extend the literature on the relationship between negative supervisory behavior and IWB, we investigate the effect of SKHS on supervisee IWB.…”
Section: Innovative Work Behaviormentioning
confidence: 99%
“…The enhanced/diminished self-efficacy then motivates/demotivates supervisees to increase/decrease their IWB, respectively (Haase et al, 2018). Using multi-level data from 83 team leaders and 466 team members in the banking sector in China, Yang et al (2017) suggested that self-efficacy mediated the positive relationship between servant leadership and creativity, On the other hand, using data from a sample of 325 employees from 17 companies in Nepal, Rauniyar et al (2017) suggested that creative self-efficacy mediated the negative relationship between abusive supervision and employee creativity. In other words, self-efficacy acts as the underlying mechanism through which positive/negative supervisory behaviors translate into enhanced/diminished IWB.…”
Section: Mediation Of Self-efficacy Between Skhs and Supervisee Iwbmentioning
confidence: 99%
“…Recent studies have found a significant relationship between servant leadership and innovation (e.g. Yang et al, 2017;Yoshida, 2014). However, to the best of our knowledge, little research has explored the underlying mechanisms that explain this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified that the influence of servant leadership on different outcomes, including creativity, may be indirect. It is therefore necessary to study the mediating mechanisms in the relationship between servant leadership and different outcomes (Liden et al, 2014;Yang et al, 2017). Servant leadership places emphasis on the personal growth of followers and adds the component of social responsibility to transformational leadership (Graham, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Jaramillo, Grisaffe, Chonko, and Roberts (2009), and Black (2010) found that servant leadership led to a decrease in turnover intention because a positive work environment was established, thus leading employees to feel more committed to the organization. Another benefit of servant leadership was reported by Yang, Liu, and Gu (2017) who found that servant leadership increased creativity at both the individual and team levels.…”
Section: Outcomes Of Servant Leadershipmentioning
confidence: 92%